2018
DOI: 10.1111/tmi.13027
|View full text |Cite
|
Sign up to set email alerts
|

Peg‐interferon and ribavirin treatment in HIV/HCV co‐infected patients in Thailand: efficacy, safety and pharmacokinetics

Abstract: PR treatment has comparable response rates and toxicity profile in Thai HIV/HCV co-infected patients as in Western HIV/HCV patients. However, ribavirin plasma concentrations were comparable with previously published studies in HIV/HCV co-infected patients, but both, just as SVR rate, were lower than in mono-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(42 reference statements)
2
2
0
Order By: Relevance
“…Although they are not listed in the drug labels, they indicate the possible adverse events in the treatment of ribavirin-interferon combination. A prospective multicenter study in Thailand [ 17 ] showed that a patient with HCV and HIV had severe hemoptysis after treatment with ribavirin-interferon combination and was consistent with our signal detection results. ADEs cannot be easily detected in studies conducted before the drug reaches the market; new adverse reports may appear after the drug is marketed, while the update of the drug label is lagging behind.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although they are not listed in the drug labels, they indicate the possible adverse events in the treatment of ribavirin-interferon combination. A prospective multicenter study in Thailand [ 17 ] showed that a patient with HCV and HIV had severe hemoptysis after treatment with ribavirin-interferon combination and was consistent with our signal detection results. ADEs cannot be easily detected in studies conducted before the drug reaches the market; new adverse reports may appear after the drug is marketed, while the update of the drug label is lagging behind.…”
Section: Discussionsupporting
confidence: 90%
“…In a multicenter trial [ 16 ], one patient stopped treatment at the 42nd week of treatment due to the decrease of platelet to 45000/mm 3 . In another study [ 17 ], a case of death due to combined treatment was reported. At the start of treatment, the patient already had a rather low platelet count; the platelet further drops after the combined treatment and finally leads to death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominance of subtype 1b corroborates earlier reports on the subtype as the predominant HCV subtype across the globe [4,11]. In addition to the cases of dual 'mixed' genotype infections identified in this study, several cases involving a mixture of more than two genotypes and/or subtypes in patients were reported in Indonesia, Vietnam, and Thailand [28,80,93]. Expectedly, such infected individuals would require more than the usual combinations of the available HCV drugs for optimal treatment outcomes.…”
Section: Plos Onesupporting
confidence: 91%